Penegakan Hukum dalam Pelayanan Pemungutan Pajak Kendaraan Bermotor (PKB) di Kantor Unit Pelaksana Teknis Pengelolaan Pendapatan Daerah (UPT PPD) Pandan, Provinsi Sumatera Utara - Posma Tumanggor; Rizkan Zulyadi; Taufik Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to find out the legal arrangements, law enforcement obstacles and how to overcome them in collecting Motor Vehicle Tax (PKB) at the Pandan Regional Revenue Management Technical Implementation Unit Office (UPTPPD) based on the legal regulations in force in Pandan Region. The research method used in this research is Normative Juridical by searching and collecting data through library research from reading sources in the form of related legal books, opinions of legal experts, related laws and regulations, related websites and interview results. The results of the study show that the implementation of PKB collection at the Provsu BPPRD starts from registration, determination, payment by the taxpayer and validation to the deposit to the regional treasury by carrying out based on the Permen, Permendagri, Pergubsu that apply at UPT PPD Pandan as a form of implementation of Law no. 28 of 2009 concerning Regional Taxes and Levies. Furthermore, regarding obstacles in the implementation of motorized vehicle tax collection at the Regional Tax and Retribution Management Agency of North Sumatra Province, are the inclusion of the owner's identity (KTP and SIM) according to the tax note/STNK, technical gaps in service to taxpayers, PKB payments with the online system, payments via Banks, the large number of motor vehicle tax arrears objects both caused by the negligence of taxpayers in fulfilling their obligations to pay taxes.